Kacio Batusangakar Outlet E-Commerce Information System Design Using the YII2 Framework - Miftahurrazi, Miftahurrazi; Slamet, Legiman (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
According to Presidential Decree No. 99 of 1998, the replacement of small businesses with business sectors which are predominantly small business activities and need to be protected to prevent unhealthy business competition. In the development of information technology, especially in the field of internet, it is a global network that unites computer networks and interactions between one another throughout the world. The aim is by connecting the network with the producer's computer to the internet, the producer can establish relationships with buyers or customers more efficiently. In this final assignment we use the E-Commerce information system method with the YII 2 framework. And in this final assignment we produce an E-Commerce information system for the Kacio outlet in the Batusangkar area using the YII 2 Framework. By using E-Commerce marketing can be done anywhere and anytime because customers only need to access the website that has been provided.